Advances in the multifunctional roles of CX3CL1 in the central nervous system - Chen, Yuhui; Liu, Junli; Zhang, Sen; Gao, Mengke; Wang, Fan; Cai, Min; Lu, Chengbiao; Li, Shaomin; Zhao, Jianhua (Frontiers in Aging Neuroscience, 2026)
C-X3-C motif chemokine ligand 1 (CX3CL1), a structurally unique chemokine in the central nervous system (CNS), shapes physiological and pathological processes via specific binding to its receptor, C-X3-C motif chemokine receptor 1 (CX3CR1). Empirical evidence indicates that this signaling axis exerts dual neuroinflammatory effects: It restrains microglial hyperactivation, yet can promote inflammation under conditions such as chronic stress. Notably, it preserves synaptic plasticity and facilitates remyelination. Age-associated reductions in CX3CL1 exhibit a strong correlation with cognitive decline; administration of exogenous CX3CL1 partially mitigates these deficits. This study provides a comprehensive account of the multifaceted functions and regulatory mechanisms of CX3CL1 in CNS diseases, thereby establishing a basis for potential new therapeutic targets.